Pathways to the Paralympic Games: Exploring the Sporting Journeys of High Performance Para Athletes with a Limb Deficiency - Hogg, Loretta Rose (Auckland University of Technology, 2018)
Characteristics associated with sport expertise have been well researched for able-bodied athletes, however, little has been documented for Para athletes. It is important to understand the sporting journeys of successful Paralympians to better support the development of future elite Para athletes. This ‘Pathways to the Paralympic Games’ research explores the sporting experiences of New Zealand Paralympians and focuses on sport expertise development in Para athletes with a limb deficiency. In-depth, semi-structured interviews were conducted with nine recent Paralympians with a limb deficiency to understand their sporting pathway, as well as any perceived influences on participation and sporting success for this population. Three key influences on the sporting pathway emerged: Sport influences, the extrinsic motivations for involvement in sport (both able-bodied and Para sport); psychological influences, the intrinsic factors that have influenced involvement; and impairment influences, the Paralympians thoughts and feelings about limb deficiency and sport. Feelings of support from coaches, parents and peers were considered to be particularly important to the Paralympians, who stated that people contributed to the positive vibe and successful culture surrounding their Para sport environment. Perceptions of sporting competence were increased and influenced through the Paralympian’s ability to apply mental skills training though techniques such as visualisation and positive self-talk. Feelings surrounding impairment were often that of frustration. This was due to both society creating pre-conceived ideas of what people living with a limb deficiency should be able to accomplish and prosthetic technology not being accessible or meeting the requirements for the level of training necessary for the Paralympian to achieve, what they perceived to be, their optimal performance. The main findings of this study suggest Paralympians have additional requirements to able-bodied high performance athletes and that having strong support networks and the ability to access appropriate resources are critical to influencing successful sporting pathways to elite Para sport. The results from this study present an evidence-base which can give insight to New Zealand’s Para sport sector on potential areas to improve future talent identification and development of emerging Para athletes.
Keywords: Para sport; Paralympics; Paralympian; Limb deficiency; Qualitative; Template Analysis; Prosthetic technology; Disability sport